Pengaruh Ukuran Baut untuk Mengurangi Kegagalan Sambungan Pada Fleksibel Kopling Flange Di Unit Thermal Oil Heater - Paul K S Harefa; Irwansyah Irwansyah; Herry Darmadi; Naqasya Asyrori Sidabutar; Dian Kurnia (JURNAL VOKASI TEKNIK, 2024)
In the industry, the use of a Thermal Oil Heater (TOH) is employed to generate a heating system by heating oil, which will be used in the production process in units that require a heating system. In the TOH unit, a pump is used to transfer the fluid, where the pump's connection uses a flange coupling to link the motor and magnetic pump for transferring thermal oil. The size and material of the bolts and nuts in the flange coupling are crucial to ensure operational safety and efficiency, taking into account rotation, power, and thermal expansion. Through observation, documentation, interviews, and literature studies, the research shows that the optimal nominal bolt diameter is 9.52 mm with a coupling distance of 60 mm, in accordance with industry standards such as the American National Standards Institute (ANSI), the International Organization for Standardization (ISO), and the Japan International Standard (JIS) to prevent joint failure and damage to the flange coupling